The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fimmu.2022.916934
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of T Helper 17 Cells May Mediate the Abnormal Humoral Immunity in IgA Nephropathy and Inflammatory Bowel Disease Based on Shared Genetic Effects

Abstract: BackgroundIgA nephropathy (IgAN) is the most frequent glomerulonephritis in inflammatory bowel disease (IBD). However, the inter-relational mechanisms between them are still unclear. This study aimed to explore the shared gene effects and potential immune mechanisms in IgAN and IBD.MethodsThe microarray data of IgAN and IBD in the Gene Expression Omnibus (GEO) database were downloaded. The differential expression analysis was used to identify the shared differentially expressed genes (SDEGs). Besides, the shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…identified CFB, a shared risk locus for the two diseases, that functions in complement activation [ 95 ]. The search for genes susceptible to both diseases is ongoing [ 96–98 ], and our study contributes to the exploration of its potential role. Regarding the prospects in clinical therapeutics, our findings can serve as novel diagnostic biomarkers and clinical treatment guidance for patients with IBD and IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…identified CFB, a shared risk locus for the two diseases, that functions in complement activation [ 95 ]. The search for genes susceptible to both diseases is ongoing [ 96–98 ], and our study contributes to the exploration of its potential role. Regarding the prospects in clinical therapeutics, our findings can serve as novel diagnostic biomarkers and clinical treatment guidance for patients with IBD and IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…These include Th17 cell differentiation, cellular senescence, and the MAPK and PI3K-Akt signaling pathways. It has been shown that the abnormal humoral immunity observed in IgA nephropathy may be mediated by the differentiation of T helper 17 cells [9] and kidney senescence is well documented to occur after injury [10]. It has been observed that Akt activation is increased in experimental tubulointerstitial fibrosis [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis showed that there were 11 types of immune cells with significant differences in the degree of infiltration between SCM myocardial tissue and normal tissue. Th17 cells play an important role in the regulation of immune-related diseases ( 42 ), and previous findings suggest that an increase in neutrophils and Th17 cells may lead to a decrease in immune system defenses in patients with sepsis ( 43 , 44 ); Studies on Tfh cells have shown that Tfh cells are associated with mortality warnings in patients with sepsis, and low Tfh cell levels may imply a poor prognosis for patients ( 45 ); Danahy et al 's research shows that in sepsis, not only the total number of CD8 + T cells decreases, but also the antigen-driven proliferation capacity and effector function of CD8 + T cells are also impaired ( 46 ); These are consistent with the results of our immune infiltration analysis, which further confirmed the important role of abnormal immune response in the pathogenesis and progression of SCM.…”
Section: Discussionmentioning
confidence: 99%